CONCEPTUALISING CSR COMMUNICATION: EXPLORING THE MODERATING ROLE OF OPINION LEADERS ON ORGANISATIONCOMMUNITY DIALOGUE - Ammar Redza, Ahmad Rizal; Dayang Aizza Maisha, Abang Ahmad; Humaira, Raslie (2021)
Corporate organisations have been subjected to high criticisms due to the misuse of Corporate Social Responsibility (CSR) communication in building the trust of the local communities. Constructed on the different approaches of community engagement initiatives, the communities’ trust is central in ensuring the organisation’s ability to obtain its Social License to Operate (SLO). Despite its importance, there is a lack of empirical attention and effort in developing a communicative framework that analyses organisation’s CSR Communication with local communities. In this article, the CSR Communication framework deliberates and expands the mechanistic perspective of communication by exploring the moderating role of opinion leaders in strengthening the relationship between the postulated corresponding variables. The use of this framework is expected to facilitate future analysis that supplies fresh insights on the relationship between the Organisation’s CSR Communication initiatives, Opinion Leaders, and Local Communities